2019
DOI: 10.1177/2050312119866944
|View full text |Cite
|
Sign up to set email alerts
|

Evolving ethics, policy and reimbursement issues of vascularized composite allotransplantation: Symposium summary

Abstract: In this article, we present a report from a national meeting titled, “Evolving Issues of Vascularized Composite Allotransplantation—A Symposium on Ethics, Policy, and Reimbursement Issues,” which convened in September 2017. We discuss the maturation of vascularized composite allotransplantation from an emerging technology to becoming an extension of clinical practice for select patients with complex reconstructive needs. Viewpoints and action items were presented by and discussed among the 70+ clinicians, rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…In the US, the Organ Procurement and Transplantation Network (OPTN) oversees organ donation and transplantation under the United Network for Organ Sharing (UNOS). Since 2014, the OPTN Final Rule added VCAs to the definition of 'organs' under its governance [32,47,48].…”
Section: Andandmentioning
confidence: 99%
See 2 more Smart Citations
“…In the US, the Organ Procurement and Transplantation Network (OPTN) oversees organ donation and transplantation under the United Network for Organ Sharing (UNOS). Since 2014, the OPTN Final Rule added VCAs to the definition of 'organs' under its governance [32,47,48].…”
Section: Andandmentioning
confidence: 99%
“…It is also difficult to perform a cost analysis due to the variable procedures and frequent lack of appropriate alternatives for comparison. A time trade-off survey study calculated quality-adjusted life years to compare costs of upper extremity VCA, including perioperative care and lifelong immunosuppression, to that of prostheses, including initial costs and maintenance requirements, and found that bilateral, but not unilateral, hand transplantation was costeffective [14,47,53]. Limitations to this analysis include inability to financially quantify the improvement in quality of living with a transplanted arm compared to a prosthesis, which do not return sensation, fine motor control, or tactile aesthetics of human tissue as VCA can [29].…”
Section: Andandmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper extremity VCA is one of several treatment options (e.g., myoelectric and mechanical prostheses) for people with UE amputations. UE VCA is an innovative treatment modality that restores body wholeness and function for patients with complex reconstructive needs ( Rose et al, 2019 ). Evidence suggests that people with UE amputations lack awareness and knowledge of UE VCA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the functional outcomes achieved by these evolving surgical techniques, recent research approaches have shown that psychosocial and bioethical issues significantly influence the outcomes [1 ▪▪ ]. VCA, particularly in the case of UETx and FTx but also in UTx (by providing the ability to give birth), restores body wholeness and function for patients with complex reconstructive needs [2]. In the introductory phase of a novel type of transplantation, with unknown medical and psychological risks, it is of great importance to follow the patients concerning all aspects of their health.…”
Section: Introductionmentioning
confidence: 99%